Development of Banff Classification from 1991 to 2019 for identifying renal allograft rejection: a narrative review for nephrologists - Dhrolia, Murtaza; Ahmad, Aasim (Journal of the Pakistan Medical Association, 2022)
Renal pathologists, nephrologists and transplant surgeons held a meeting in 1991 at Banff, Canada, and developed a classification scheme that standardised the international classification of renal allograft biopsies and called it the Banff Classification. Following the first meeting, 15 meetings were held, usually every two years, that revised the classification in the light of new evidence and techniques. The latest printed consensus was after the 2019 meeting in Pittsburgh in the United States of America. Several articles have been published in the last 30 years that have created ambiguities for nephrologists and have made things challenging for the expert pathologists. The current perspective review was planned to make it easy and clear for beginners and for practitioners how the Banff Classification has evolved since its inception. Key Words: Development, Banff classification, Renal allograft rejection.